2012
DOI: 10.1002/jsfa.5634
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hygiene practices and microbiological status of ready‐to‐eat vegetable salads in Spanish school canteens

Abstract: This study constitutes a descriptive analysis of the hygiene/sanitation conditions implemented in food service systems in eight Spanish school canteens. The results should help risk managers to better define control measures to be adopted in order to prevent foodborne infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
4
12
0
2
Order By: Relevance
“…Regarding table cleaning, only 52.6% of the study food services cleaned tables properly, corroborating a study done in school canteens in Andalusia (Spain) that found unsatisfactory table cleaning and disinfection conditions 25 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Regarding table cleaning, only 52.6% of the study food services cleaned tables properly, corroborating a study done in school canteens in Andalusia (Spain) that found unsatisfactory table cleaning and disinfection conditions 25 .…”
Section: Discussionsupporting
confidence: 83%
“…In Andalusia, Spain, the food handlers in 35.0% of the school canteens did not wash their hands properly, and in some canteens food handlers did not wash their hands at all 25 . The findings for the study food services were similar, except for hand washing frequency because 80.9% of the interviewed food handlers complied with the legislation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De hecho, las normativas vigentes no mencionan el uso de guantes como medida para preservar la higiene de los alimentos. Aunque no se considera incorrecto, actualmente se recomienda no utilizarlos, ya que un uso inadecuado puede provocar problemas de contaminación cruzada similares a los que suceden cuando no hay una limpieza de manos correcta 13,22,23 . En relación al servicio de los menús, cabe destacar que un alto porcentaje de los centros declaran tomar medidas para evitar la contaminación cruzada.…”
Section: Discussionunclassified
“…In terms of food safety, other studies mainly dealt with food analysis to ascertain or prevent acute food intoxication from pathogens such as viruses and bacteria (Osimani et al 2011;Rodríguez-Caturla et al 2012). As regards chemical contamination of school meals, recent papers have focused on polychlorodibenzo-p-dioxins and polychlorodibenzofurans (PCDD-Fs) (Mayer 2001), acrylamide as a process contaminant (Mestdagh et al 2007), and metals (Bastías et al 2010).…”
mentioning
confidence: 99%